Cecal Metabolome Profiles of Turkey Poults in Response to Salmonella Heidelberg Challenge with or Without Turkey-Derived Lactobacillus Probiotic and Trans-Cinnamaldehyde - Grace Dewi; Ranjith Ramanathan; Anup Kollanoor Johny (Animals, 2025)
Salmonella colonization in the gastrointestinal tract of turkeys presents a risk to the safety of products derived from them. Lactobacillus-based probiotics and a plant-derived compound, trans-cinnamaldehyde, have previously been found to be effective in reducing multidrug-resistant Salmonella enterica subsp. enterica serovar Heidelberg (S. Heidelberg) in turkey poults. However, the effect of the challenge and the application of the treatments on the cecal metabolome has yet to be elucidated. Thus, the objective of the present study was to characterize alterations in the metabolic profiles of cecal contents collected from poults following S. Heidelberg challenge and treatment with Lactobacillus salivarius UMNPBX2 and L. ingluviei UMNPBX19 (LB), trans-cinnamaldehyde (TC), or a combination of both (CO) using untargeted gas chromatography–mass spectrometry (GC-MS). Poults in the challenged control (PC) group had the most distinct and convergent metabolome profiles, with the most pronounced disparity observed compared to the unchallenged control (NC), indicating the effect of the S. Heidelberg challenge. Perturbations in metabolites in the primary bile acid biosynthesis, pentose and glucuronate interconversions, and steroid biosynthesis were the most prominent. The greater abundance of metabolites, such as primary bile acids and sugars, in the PC group may be associated with S. Heidelberg colonization or potential shifts in microbiota. The treatments yielded varying effects on the metabolome profiles, with the TC and CO groups exhibiting the closest similarity, although TC was more similar to NC. The findings revealed alterations to ceca-associated metabolites, which are likely a response to the S. Heidelberg challenge and the application of the TC and LB treatments. Additional studies are needed to validate the possible causal relationship between the observed shifts. Gaining insight into the alterations to the metabolic microenvironment in the avian cecum will help elucidate the mechanisms by which they facilitate Salmonella persistence. Understanding these relationships can aid in designing more effective pre-harvest Salmonella control strategies and enhancing the efficacy of interventions within the flock.